Historical Learning Model Design Based On Critical Literation In The Era And Post Covid-19 - Mahdiana, Nabillah; Sariyatun, Sariyatun; Purwanta, Hieronymus (Universitas Sebelas Maret, 2020)
This research is motivated by the situation during the Covid-19 period which affects all sectors of life, including in the world of education. Teachers and students are required to be literate towards technology and literacy in learning to anticipate the spread of false information or hoaxes. The methodology used in this research is qualitative with descriptive analysis and data collection techniques in the form of a literature study. The findings of this study lead to the conclusion that the critical literacy-based historical learning model is important to apply because it is beneficial for teachers and students. The critical literacy learning model is designed with a critical pedagogical approach changing the wording hone critical thinking skills and to equip students with the skills to understand, critique texts critically, analytically, and evaluatively. While the benefits for teachers are an effort to improve the quality and effectiveness of learning by developing 21st-century competence.